2014
DOI: 10.1158/1538-7445.am2014-3203
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3203: Honokiol inhibits growth and migration of renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is a common urological cancer worldwide and is known to the high risk of recurrence and metastasis. Approximately 70% of patients with RCC will develop recurrence after surgical resection, and 25%-30% of patients will eventually develop progression to distant metastasis. Honokiol is a small-molecule polyphenol isolated from the genus Magnolia, which has been shown to be a potential anticancer agent in multiple facets of signal transduction. Here we demonstrate that honokiol inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Honokiol (HK: Fig. 1A ) is a bio-active component of the bark of the Chinese traditional herb Magnolia officinals 8 . Previous studies have demonstrated the variety of pharmacological effects of HK, including anti-oxidative, anti-depressant, and anti-inflammatory effects 9 10 11 .…”
mentioning
confidence: 99%
“…Honokiol (HK: Fig. 1A ) is a bio-active component of the bark of the Chinese traditional herb Magnolia officinals 8 . Previous studies have demonstrated the variety of pharmacological effects of HK, including anti-oxidative, anti-depressant, and anti-inflammatory effects 9 10 11 .…”
mentioning
confidence: 99%